2014
DOI: 10.1001/jamasurg.2013.4146
|View full text |Cite|
|
Sign up to set email alerts
|

Reappraisal of Central Pancreatectomy

Abstract: Central pancreatectomy is associated with an excellent pancreatic function at the expense of a significant morbidity and a non-nil mortality rate,underestimated by the published literature. The procedure is best indicated for benign or low-grade lesions in young and fit patients who can sustain a significant postoperative morbidity and could benefit from the excellent long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(36 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…The high level of complexity of this technique should be noted, as well as the probable higher rate of pancreatic fistula during the postoperative period (1,3,5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The high level of complexity of this technique should be noted, as well as the probable higher rate of pancreatic fistula during the postoperative period (1,3,5).…”
Section: Resultsmentioning
confidence: 99%
“…When it comes to dealing with benign lesions of the isthmus and proximal body of the pancreas which cannot be treated with enucleation (large lesions or lesions close to the duct of Wirsung), the usual techniques performed are a distal pancreatectomy (DP) or central pancreatectomy (CP) (3)(4)(5). The classic approach with DP involves the complete resection of the body and tail of the pancreas; however, CP allows the preservation of the distal pancreas, without the need of a splenectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from the literature have shown that overall morbidity after CP ranges from 29 to 92% and the POPF rate ranges from 7.5 to 100% [4, 18-26]. Different assessments and definitions of POPF may explain such a large range of rates of POPF after CP or DP.…”
Section: Discussionmentioning
confidence: 99%